1990
DOI: 10.1073/pnas.87.9.3343
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione regulates activation-dependent DNA synthesis in highly purified normal human T lymphocytes stimulated via the CD2 and CD3 antigens.

Abstract: Regulation of proliferation of normal human T lymphocytes (T cells) by glutathione (GSH) was explored with T-cell activation models that-do not require accessory cell signals. L-Buthionine-(S,R)-sulfoximine (BSO), which inactivates y-glutamylcysteine synthetase and therefore inhibits GSH synthesis, inhibited proliferation elicited by monoclonal antibodies directed at cluster designation 2 (CD2) and CD3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(189 citation statements)
references
References 46 publications
9
178
2
Order By: Relevance
“…In contrast to the positive effects of H 2 0 2 observed on gene expression, exposure of ESb-L cells to H202 was largely growth-inhibitory. This is consistent with the general requirement of thiols for lymphoid cells and with reports that withdrawal of thiols inhibits lymphocyte proliferation [25][26][27]. However, we observed that in a limited range of small H202 concentrations proliferation was enhanced when the cells were kept in a reducing environment, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the positive effects of H 2 0 2 observed on gene expression, exposure of ESb-L cells to H202 was largely growth-inhibitory. This is consistent with the general requirement of thiols for lymphoid cells and with reports that withdrawal of thiols inhibits lymphocyte proliferation [25][26][27]. However, we observed that in a limited range of small H202 concentrations proliferation was enhanced when the cells were kept in a reducing environment, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, intracellular ROI formation has been proposed to be required for lymphocyte proliferation since various antioxidants inhibit cell growth in response to mitogens [4,21,22]. By contrast, the proliferative response in other situations, such as in mixed lymphocyte reactions or IL-2-dependent cell growth, was found to be inhibited by prooxidants and promoted by antioxidants and exogenous thiols [5,[23][24][25][26][27][28]. Thus, it appears that certain lymphocyte functions are obviously promoted by prooxidant conditions whereas others are inhibited, suggesting the requirement of a delicate redox balance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, we speculate that aberrant glutathione levels and redox homeostasis cause the increased division and small-cell phenotypes observed in the smt15-1 mutant. Supporting this hypothesis are numerous reports on the close association between cell proliferation and elevated glutathione levels and high GSH-GSSG ratios (Mauro et al, 1969;Kosower and Kosower, 1978;Suthanthiran et al, 1990;Sánchez-Fernández et al, 1997;May et al, 1998;Nkabyo et al, 2002). We have not been able to examine temporal redox control at a finer scale in wild-type and smt15-1 cells, as has been done in budding yeast, where redox and respiratory activity cycle with a period of about 40 min (Tu et al, 2005).…”
Section: Smt15 Glutathione and Cell Cycle Controlmentioning
confidence: 68%
“…A 10 -40% decrease in GSH content can completely inhibit lymphocyte activation in vitro (8). Indeed, the very fact that Tat modulates GSH biosynthesis in addition to suppressing the activity of manganese superoxide dismutase (27,41,42) may testify to the importance of redox regulation in HIV pathogenesis.…”
Section: Fig 3 Gcs-ls Protein Content Is Decreased In Liver and Erymentioning
confidence: 99%